Spatial competition with demand uncertainty: A laboratory experiment - Bonein, Aurélie; Turolla, Stéphane (Journal of economics & management strategy, 2023)
Motivated by recent research on product differentiation, we conduct laboratory experiments to study how demand uncertainty influences firms' incentives to differentiate. We ground our experiment on a discrete version of the standard location‐then‐price game introduced by Hotelling (1929), and we consider different levels of demand uncertainty. We first derive the game equilibrium assuming risk‐neutral firms, and obtain the standard prediction that a high level of demand uncertainty generates more differentiation. Second, we extend the analysis to consider non‐risk neutral firms and markets with asymmetric risk profiles. We show that the game equilibrium can differ substantially according to the attitude to risk. Third, we compare our predictions with the experimental data and find that demand uncertainty acts as a differentiation force in the context of both symmetric markets composed of risk‐neutral or risk‐lover subjects and asymmetric markets. We find support also for the agglomeration effect arising from demand uncertainty for sufficiently risk‐averse subjects. Overall, these results might explain the opposite product differentiation strategies frequently observed in markets with fast‐evolving tastes (i.e., minimum or maximum differentiation). Finally, the data confirm that subjects differentiate to relax price competition and provide evidence of a strong positive relationship between differentiation and prices.